An efficient routing protocol for green communications in vehicular ad-hoc networks. - Toutouh-el-Alamin, Jamal; Alba-Torres, Enrique (ACM, 2011)
Vehicular ad-hoc networks (VANETs) provide the communications required to deploy Intelligent Transportation Systems (ITS). In the current state of the art there is a lack of studies on Green Communications (energy-efficiency) in VANETs. However, due to the possible interaction with devices that are fed with different electrical sources and the proliferation of electrical vehicles, the power consumption by the wireless communications might become a major concern in VANET design. In this paper, we study the energy-efficiency of a quality-of-service optimized version of OLSR by means of Differential Evolution (DE-OLSR). We have conducted a series of VANET simulations aiming at analyzing the power consumption and the QoS in order to compare DE-OLSR with the standard version of OLSR. An extensive performance evaluation shows that DE-OLSR clearly outperforms the standard version in terms of energy consumption, while offering a competitive QoS.
Política de acceso abierto tomada de: https://www.acm.org/publications/openaccess#h-green-open-access
Keywords: Sistemas inteligentes de transporte; Heurística; Optimización matemática; Metaheuristics; Optimization; Vehicular ad hoc networks; Green communication